Innate immune cell activation after HIV-1 vaccine administration is associated with increased antibody production - N’guessan, Kombo F.; Machmach, Kawthar; Swafford, Isabella; Costanzo, Margaret C.; Wieczorek, Lindsay; Kim, Dohoon; Akapirat, Siriwat; Polonis, Victoria R.; Pitisuttithum, Punnee; Nitayaphan, Sorachai; Gurunathan, Sanjay; Sinangil, Faruk; et al. (Frontiers in Immunology, 2024)
The RV144 Thai phase III clinical trial's canarypox-protein HIV vaccine regimen showed modest efficacy in reducing infection. We therefore sought to determine the effects of vaccine administration on innate cell activation and subsequent associations with vaccine-induced immune responses. RV306 was a randomized, double-blind clinical trial in HIV-uninfected Thai adults that tested delayed boosting following the RV144 regimen. PBMC collected from RV306 participants prior to and 3 days after the last boost were used to investigate innate immune cell activation. Our analysis showed an increase in CD38+ mucosal associated invariant T (MAIT) cells, CD38+ invariant natural killer T (iNKT) cells, CD38+ gd T cells, CD38+, CD69+ and HLA-DR+ NK cells 3 days after vaccine administration. An increase in CD14-CD16+ nonclassical monocytes and CD14+CD16+ intermediate monocytes accompanied by a decrease in CD14+CD16-classical monocytes was also associated with vaccine administration. Inclusion of ALVAC-HIV in the boost did not further increase MAIT, iNKT, gd T, and NK cell activation or increase the proportion of non-classical monocytes. Additionally, NK cell activation 3 days after vaccination was positively associated with antibody titers of HIV Envspecific total IgG and IgG1. Vd1 T cell activation 3 days after vaccine administration was associated with HIV Env-specific IgG3 titers. Finally, we observed trending associations between MAIT cell activation and Env-specific IgG3 titers and between NK cell activation and TH023 pseudovirus neutralization titers. Our study identifies a potential role for innate cells, specifically NK, MAIT, and gd T cells, in promoting antibody responses following HIV-1 vaccine administration.